Assessment and characterization of the total geometric uncertainty in Gamma Knife radiosurgery using polymer gels. Issue 3 (8th February 2013) - Moutsatsos, A.; Karaiskos, P.; Petrokokkinos, L.; Sakelliou, L.; Pantelis, E.; Georgiou, E.; Torrens, M.; Seimenis, I.
Abstract : Purpose: : This work proposes and implements an experimental methodology, based on polymer gels, for assessing the total geometric uncertainty and characterizing its contributors in Gamma Knife (GK) radiosurgery. Methods: : A treatment plan consisting of 26, 4‐mm GK single shot dose distributions, covering an extended region of the Leksell stereotactic space, was prepared and delivered to a polymer gel filled polymethyl methacrylate (PMMA) head phantom (16 cm diameter) used to accurately reproduce every link in the GK treatment chain. The center of each shot served as a "control point" in the assessment of the GK total geometric uncertainty, which depends on (a) the spatial dose delivery uncertainty of the PERFEXION GK unit used in this work, (b) the spatial distortions inherent in MR images commonly used for target delineation, and (c) the geometric uncertainty contributor associated with the image registration procedure performed by the Leksell GammaPlan (LGP) treatment planning system (TPS), in the case that registration is directly based on the apparent fiducial locations depicted in each MR image by the N‐shaped rods on the Leksell localization box. The irradiated phantom was MR imaged at 1.5 T employing a T2‐weighted pulse sequence. Four image series were acquired by alternating the frequency encoding axis and reversing the read gradient polarity, thus allowing the characterization of the MR‐related spatial distortions. Results: : MR spatial distortions stemming from main field ( B 0 ) inhomogeneity as well as from susceptibility and chemical shift phenomena (also known as sequence dependent distortions) were found to be of the order of 0.5 mm, while those owing to gradient nonlinearities (also known as sequence independent distortions) were found to increase with distance from the MR scanner isocenter extending up to 0.47 mm at an Euclidean distance of 69.6 mm. Regarding the LGP image registration procedure, the corresponding average contribution to the total geometric uncertainty ranged from 0.34 to 0.80 mm. The average total geometric uncertainty, which also includes the GK spatial dose delivery uncertainty, was found equal to (0.88 ± 0.16), (0.88 ± 0.26), (1.02 ± 0.09), and (1.15 ± 0.24) mm for the MR image series acquired with the read gradient polarity (direction) set toward right, left, posterior, and anterior, respectively. Conclusions: : The implemented methodology seems capable of assessing the total geometric uncertainty, as well as of characterizing its contributors, ascribed to the entire GK treatment delivery (i.e., from MR imaging to GK dose delivery) for an extended region of the Leksell stereotactic space. Results obtained indicate that the selection of both the frequency encoding axis and the read gradient polarity during MRI acquisition may affect the magnitude as well as the spatial components of the total geometric uncertainty.